Patterns of abuse amongst Sri Lankan women returning home after working as domestic maids in the Middle East: An exploratory study of medico-legal referrals. (January 2017) - Wickramage, Kolitha; De Silva, Malintha; Peiris, Sharika
Abstract: Objective: Migrant worker abuse is well recognised, but poorly characterised within the scientific literature. This study aimed to explore patterns of abuse amongst Sri Lankan women returning home after working as domestic maids. Methods: Sri Lanka has over 2 million of its citizens employed overseas as international labor migrants. A cross-sectional study was conducted on Sri Lankan female domestic maids returning from the Middle East region who were referred for medico-legal opinion. Results: A total of 20 women were included in the study. Average length of their employment overseas was 14 months. Complaints of physical violence directed mainly through their employers were made by 60% of women. Upon physical examination, two-thirds had evidence of injuries, with a third being subjected to repetitive/systematic violence. Eighty percent suffered some form of psychological trauma. Personal identity papers and travel documents had been confiscated by the employer in 85% of cases, with two thirds indicating they were prevented and/or restricted from leaving their place of work/residence. Conclusions: Our study demonstrates that female domestic maid abuse manifests through multiple pathways. Violence against such workers span the full spectrum of physical, financial, verbal, emotional abuse and neglect, as defined by the World Health Organization. Findings from this exploratory study cannot be generalized to the large volume of migrant worker outflows. Further research is needed to determine incidence and define patterns in other migrant worker categories such as low-skilled male workers. Highlights: Labor migrant abuse is well recognised, but poorly characterised within scientific literature. Our study responds to a call for research evidence based on articles published in this Journal. Our study shows violence directed at migrant workers manifest across a spectrum of abusive patterns. Very few studies within literature have adopted the rigorous method to ascertain patterns of abuse. We discuss policy and programmatic strategies to address the issue.